2011
DOI: 10.1245/s10434-011-1833-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Routine Unilateral Central Neck Dissection on Preablative and Postablative Stimulated Thyroglobulin Levels after Total Thyroidectomy in Papillary Thyroid Carcinoma

Abstract: BackgroundProphylactic central neck dissection (CND) remains controversial in papillary thyroid carcinoma (PTC). Because postsurgical stimulated thyroglobulin (sTg) level is a good surrogate for recurrence, the study aimed to evaluate the impact of prophylactic CND on preablative and postablative sTg levels after total thyroidectomy.MethodsOf the 185 patients retrospectively analyzed, 82 (44.3%) underwent a total thyroidectomy and prophylactic CND (CND-positive group) while 103 (55.7%) underwent total thyroide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
113
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(117 citation statements)
references
References 27 publications
2
113
1
1
Order By: Relevance
“…(Zetoune et al,2010) Therefore, based on these findings, there might be a potential benefit of lower recurrence in those who underwent either unilateral or bilateral pCND, although larger-scale prospective studies are required to confirm this. (Lang et al,2011c) They found that the CND+ group had a significantly lower median pre-ablation stimulated Tg level (<0.5ug/L vs. 6.7ug/L,p<0.001) and achieved a higher rate of pre-ablation athyroglobulinemia (51.2% vs. 22.3%,p=0.024) than those who underwent a total thyroidectomy only but these differences were not observed 6 months after ablation. They also found that pCND was the only independent factor for pre-ablation athyroglobulinemia.…”
Section: First Author /Year Of Publicationmentioning
confidence: 96%
See 4 more Smart Citations
“…(Zetoune et al,2010) Therefore, based on these findings, there might be a potential benefit of lower recurrence in those who underwent either unilateral or bilateral pCND, although larger-scale prospective studies are required to confirm this. (Lang et al,2011c) They found that the CND+ group had a significantly lower median pre-ablation stimulated Tg level (<0.5ug/L vs. 6.7ug/L,p<0.001) and achieved a higher rate of pre-ablation athyroglobulinemia (51.2% vs. 22.3%,p=0.024) than those who underwent a total thyroidectomy only but these differences were not observed 6 months after ablation. They also found that pCND was the only independent factor for pre-ablation athyroglobulinemia.…”
Section: First Author /Year Of Publicationmentioning
confidence: 96%
“…(Lang et al,2011c) In their experience, most of the residual microscopic disease, presumably not removed by the initial pCND, was still able to be ablated by RAI ablation and so the group without pCND achieved similar stimulated Tg levels and similar rate of athyroglobulinemia 6 months after ablation. (Lang et al,2011c) The authors concluded that although performing pCND in total thyroidectomy may offer a more complete initial tumor resection than total thyroidectomy alone by minimizing any residual microscopic disease, such difference becomes less noticeable 6 months after RAI ablation. (Lang et al,2011c) The other advantage of performing pCND is the fact that the status of central lymph nodes or pN1a is better known and so more accurate staging is possible.…”
Section: First Author /Year Of Publicationmentioning
confidence: 97%
See 3 more Smart Citations